Identifying potential drug targets for myocardial infarction through Mendelian randomization. - Xiangyou Yu; Shasha Liu (PLoS ONE)
Background This study explored the associations between plasma and cerebrospinal fluid (CSF) proteins and myocardial infarction (MI) risk. Identifying specific proteins as biomarkers for MI could enhance our understanding of disease mechanisms and inform clinical practice. Methods We combined protein quantitative trait loci (pQTL) data for plasma and CSF proteins with genome-wide association study (GWAS) summary statistics for MI. Mendelian Randomization (MR) analyses were conducted to establish causal relationships, supported by Bayesian colocalization and Spearman correlation analyses. For plasma proteins, we used pQTL data from Cheng et al. to select 738 cis-acting SNPs associated with 734 proteins. The "TwoSampleMR" method and inverse-variance weighted MR were applied for evaluations. Results In plasma, CD8A and HDHD2 were identified as protective factors against MI, while DPEP1 was linked to increased risk. In CSF, CD30 Ligand was associated with MI risk. Bayesian colocalization supported the association for CD8A in plasma. No significant correlation was found between plasma and CSF results, suggesting distinct mechanisms for these biomarkers. Conclusion Our study identified several plasma and CSF proteins linked to MI risk, offering new insights into the disease's biological underpinnings. These findings could guide future research on MI biomarkers and contribute to improved prevention and treatment strategies.